Do Indonesia Islamic Banks Perform Better Than Malaysia? A Malmquist Index Approach - Uula, Mimma Maripatul; Rusydiana, Aam Slamet; Ali, Mohammad Mahbubi (Review on Islamic Accounting, 2023)
This study aims to measure the productivity of Islamic banks in Indonesia and Malaysia using the Malmquist Productivity Index (MPI) method with the research period 2010-2019. The research objects used are 23 Islamic banks in Indonesia and Malaysia. The data of this study comes from the annual financial statements of each bank from the period 2010-2019. The input variables in this study are employee costs, administrative costs and third-party funds. And for the output variable is financing and operating income. The results of this study explain that during the period 2010-2019, the productivity level of Islamic banks in Indonesia and Malaysia has a fluctuating trend from year to year. Based on the average TFPCH score, it is concluded that the productivity of Islamic banks shows no increase in productivity or constant and technological change has not contributed optimally to the increase in productivity of Islamic banks in Indonesia and Malaysia. Furthermore, analyzing individually on Islamic Banks in Indonesia and Malaysia, it is found that there are 8 Islamic Banks with increased productivity, one Islamic bank in Malaysia and seven Islamic banks in Indonesia. The results also highlighted that the productivity level of Islamic banks in Indonesia is relatively better than Islamic banks in Malaysia. Then, the Malmquist Index quadrant analysis found that Islamic Banks in Indonesia and Malaysia dominate in quadrant 3 with a total of 12 Islamic Banks, followed by quadrant 4 with a total of 7 Islamic banks, and quadrant 1 with a total of 4 Islamic banks.